Los Jansenistas y la Escuela - Pieroni Francini, Marta (Cuadernos de Historia Moderna, 2002)
This article studies the «Petites Ecoles de Port-Royal», directed by the «jansenistas» during 1637-1660, (Inc novelty experience on education, pedagogic methods and didactic forms, and its problems with the others religious teachers (jesuits) and the civil power.